2022
DOI: 10.1002/gch2.202200025
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 Nanoparticles Seed Priming Increases Salicylic Acid Level and ROS Scavenging Ability to Improve Rapeseed Salt Tolerance

Abstract: Soil salinity is a major issue limiting efficient crop production. Seed priming with nanomaterials (nanopriming) is a cost‐effective technology to improve seed germination under salinity; however, the underlying mechanisms still need to be explored. Here, polyacrylic acid coated nanoceria (cerium oxide nanoparticles) (PNC, 9.2 nm, −38.7 mV) are synthesized and characterized. The results show that under salinity, PNC priming significantly increases rapeseed shoot length (41.5%), root length (93%), and seedling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 98 publications
(133 reference statements)
3
17
0
Order By: Relevance
“…2a). This is in accordance with previous studies showed that nanoceria improved salt tolerance in rice (Zhou et al, 2021), cotton (An et al, 2020;Liu et al, 2021), rapeseed (Khan et al, 2022(Khan et al, , 2021Rossi et al, 2016Rossi et al, , 2017, cucumber (Chen et al, 2022), Arabidopsis (Wu et al, 2018a) and (d-f ) K + (d) and Na + (e) content and Na + /K + ratio (f) in the roots of rapeseed treated with control buffer, PNC or PMO under salt stress. Mean ± SE (n = 8) (g and h) The relative expression level of K + and Na + transport related genes in the leaves (g) and roots (h) of rapeseed treated with control buffer, PNC or PMO under salt stress.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…2a). This is in accordance with previous studies showed that nanoceria improved salt tolerance in rice (Zhou et al, 2021), cotton (An et al, 2020;Liu et al, 2021), rapeseed (Khan et al, 2022(Khan et al, , 2021Rossi et al, 2016Rossi et al, , 2017, cucumber (Chen et al, 2022), Arabidopsis (Wu et al, 2018a) and (d-f ) K + (d) and Na + (e) content and Na + /K + ratio (f) in the roots of rapeseed treated with control buffer, PNC or PMO under salt stress. Mean ± SE (n = 8) (g and h) The relative expression level of K + and Na + transport related genes in the leaves (g) and roots (h) of rapeseed treated with control buffer, PNC or PMO under salt stress.…”
Section: Discussionsupporting
confidence: 93%
“…2a). This is in consistent with previous studies, which showed that rapeseed primed with PNC treated plants showed much better root performance than control group under salt stress (An et al, 2020;Khan et al, 2021Khan et al, , 2022. Moreover, it should be noted that although CeCl 3 and MnCl 2 treatment also improved rapeseed root performance than control plants under salt stress, no significant difference of whole plant fresh weight was found among these treatment groups (Figure S2a).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations